PENERAPAN PEMBELAJARAN BERDIFERENSIASI DI SEKOLAH DASAR - Putu Dinda Purnita, Ayu; Astawan, I Gede; Desia Tristiantari, Ni Ketut (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
For education to be meaningful and student centered, primary school curricula should take into account the varied preparation levels, interests, and learning profiles of the pupils. Nevertheless, classroom practice has not fully embraced the Merdeka Curriculum framework's differentiated learning implementation. The purpose of this study was to examine the limitations faced at SD Negeri 1 Banjar Bali, teachers' comprehension and the use of differentiated learning across content, process, product, and learning environment components. A purposive sample of primary school teachers was used in a descriptive qualitative design. Non-participant observation, interviews, and document analysis were used to gather data, which were then analysed utilizing methods for data reduction, data display, and conclusion drawing. The results show that although teachers have a conceptual understanding of differentiated learning, its application is still flexible. While process and learning environment diversification is used more frequently, content and product differentiation is less effective because of time constraints, workloads, learning facilities, and difficulties with classroom management. Therefore, strengthening teachers’ practical capacity, improving infrastructure support, and allocating time for instructional development are necessary to ensure sustainable and optimal implementation of differentiated learning in elementary schools.